Factors Influencing Students’ Acceptance and Satisfaction with LMS in Blended Learning Environment - Ai-Ling Aileen Koh; Ying-Leh Ling (CV Projurnal Mitra Publikasi, 2025)
Blended learning (BL) has become an essential approach in Malaysian Technical and Vocational Education and Training (TVET), with Learning Management Systems (LMS) serving as the core platform for delivering digital instruction and learner support. However, students’ acceptance and satisfaction with LMS remain uneven, particularly in competency-based environments where learners depend heavily on practical guidance and technological support. This study examined the extent to which technological experience and knowledge sharing influence students perceived ease of use (PEOU), perceived usefulness (PU), and overall satisfaction with LMS in a blended learning environment at a Malaysian polytechnic. Using a quantitative research design, data were collected from 290 students who had used the LMS for at least one semester. Multiple regression analyses revealed that both technological experience and knowledge sharing significantly predicted PEOU, PU, and satisfaction. Technological experience emerged as the strongest contributor across all models, suggesting that students who are more technologically competent perceive the LMS as easier to use, more beneficial, and more satisfying. Knowledge sharing also played a meaningful role by enhancing students’ confidence, engagement, and perceived learning value. These findings highlight the importance of strengthening digital competencies and fostering collaborative learning practices to support effective LMS adoption. The study provides practical implications for educators and administrators seeking to optimize LMS integration in TVET-based blended learning environments.